The Scientific and Practical Significance of The Paradigm of The Development of Scientific Support of the 10th Technological Order in The World Economy - Valery Vladimirovich Glushchenko (Universitas Pendidikan Indonesia (UPI), 2023)
The subject of the article is the scientific and practical significance of the paradigm of the development of scientific support of the 10th technological order in the world economy; the object of the article is the effectiveness of the development processes of the tenth technological order in the economy and society; the purpose of the work is to increase the efficiency of the development processes of the tenth technological order; to achieve this goal, the following tasks are solved: socio-economic roles and results are described the transition of organizations to the conditions of the tenth technological order; a systematic analysis of technological orders is carried out; the image of the future tenth technological order is formed; the expediency of applying the theory of technological order in systemic unity with crisis management is justified (it is shown that this will reduce the risks of crises); indicators are given to assess the effectiveness of the processes of the organization's entry into the tenth technological order; the scientific methods of this article are: historical analysis, system analysis, comparative and logical analysis; heuristic synthesis, political science, system-analytical approach, system engineering, expert methods, efficiency theory; Scientific novelty of the work is determined by the description of the scientific and practical significance of the theory of technological regimes to reduce risks and damage from the crisis, which is associated with the formation of the tenth technological regime.